Writing Two Major Chapters of a Book on Flourishing Ethics: Sabbatical Spring 2009 - Bynum, Terrell Ward (2009)
The chapter on the information ethics of Oxford scholar, Luciano Floridi, was completed and is scheduled for publication in Floridi's anthology. The keynote address, Philosophy and the Information Revolution, presented at the Computer Ethics: Philosophical Enquiry 2009 conference in Corfu, Greece, is also scheduled for publication in the journal Ethics and Information Technology. The ideas from both articles have been included in the curriculum for the Computer Ethics class at SCSU.
Keywords: dept.phi; faculty_collection